Answer :

Given x = 1 is a root of the equation x2 + kx + 3 = 0 it means it satisfies the equation.

Substituting x = 1 in equation -


12 + k(1) + 3 = 0




Putting the value of k in the given equation : x2 + kx + 3 = 0


This reduced to the quadratic equation x2 - 4x + 3 = 0


Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation


= 1.3


= 3


And either of their sum or difference = b


= - 4


Thus the two terms are - 1 and - 3


Sum = - 1 - 3 = - 4


Product = - 1. - 3 = 3




x(x-1)-3(x-1) = 0


(x-1)(x-3) = 0


x = 1 or x = 3


Thus other root is 3.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics